Pengaruh Promo Harbolnas Terhadap Pembelian Impulsif di Shopeepay - Rio Kartika; Ine Mayuni; Dessy Damayanthy (Masyarakat Ekonomi Syariah Bogor, 2024)
The phenomenon of online shopping that causes the emergence of impulsive purchases, especially at the Shopee Harbolnas festival. The many conveniences offered and the promotional activities carried out stimulate consumers to make impulse purchases. The purpose of this study was to determine the effect of the influence of the harbolnas promo on impulse purchases at shopeepay. This research uses quantitative methods. The sample in this study amounted to 30 respondents using purposive sampling technique. The data analysis process uses simple linear regression analysis. The results of the research on harbolnas promo have a significant positive effect on impulse purchases at shopeepay. The amount of influence is 38%, the remaining 62% is influenced by other factors outside the variables not used in the study